2016
DOI: 10.1002/chem.201604062
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Nonfluorescent Conformation of AIEgen: A Tetraphenylethene Embedded in the Calix[4]arene's Skeleton

Abstract: Two novel 1,1-diphenylmethylidene decorated calix[4]arenes, (Calix-DPE(OCH ) and Calix-DPE(OH) ), were designed and prepared. The tetraphenylethene (TPE) unit is embedded in the calix[4]arenes skeleton, so the conformation of tetraphenylethene unit is significantly affected by the conformation of calix[4]arene. Unlike the Calix-DPE(OCH ) , the Calix-DPE(OH) does not show the aggregation-induced emission (AIE) phenomena in solution or the crystal state because of the presence of intramolecular hydrogen bonding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The required product 3 was obtained using column chromatography on a silica gel in a 58% yield. In the next step, the removal of the methyl ether groups was carried out with boron tribromide, which is frequently used for dealkylation reactions in calixarene chemistry [25,26]. Surprisingly, this reagent did not produce the expected dealkylated thiacalixarene 4.…”
Section: Resultsmentioning
confidence: 99%
“…The required product 3 was obtained using column chromatography on a silica gel in a 58% yield. In the next step, the removal of the methyl ether groups was carried out with boron tribromide, which is frequently used for dealkylation reactions in calixarene chemistry [25,26]. Surprisingly, this reagent did not produce the expected dealkylated thiacalixarene 4.…”
Section: Resultsmentioning
confidence: 99%
“…These three macrocycles represent the first examples of employing pillar[6]­arene as the skeleton to construct TPE-based macrocycles. Subsequently, two well-known host molecules, namely, calix[4]­arene and pillar[5]­arene, were employed (Scheme ) to construct TPE-incorporated macrocycles 63 and 64 . The characterization showed that Calix-DPE­(OMe) 4 exhibits the typical AIE property, while Calix-DPE­(OH) 4 has no emission in either solution or the solid state.…”
Section: Strategies For the Construction Of Tpe-incorporated Macrocyc...mentioning
confidence: 99%
“…Among AIEgen systems, TPE 19,20 as a type AIEgens, not only have been studied for MFC behavior by varying substituents to modify its molecular structure, 21–23 but it also has been employed as a fluorescent building block of fluorescent macrocycles 24–28 or cages 29–31 in recent years. These cyclic TPE compounds exhibit outstanding performances, which enable them as selectivity sensors, 32 molecular storage materials, 33 and supramolecular catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the AIE luminogens (AIEgens) display variable emitting color in the solid state by external stimuli for the change in molecular packing, namely MFC, [16][17][18] which are promising candidates for stimulus-responsive fluorescent materials. Among AIEgen systems, TPE 19,20 as a type AIEgens, not only have been studied for MFC behavior by varying substituents to modify its molecular structure, [21][22][23] but it also has been employed as a fluorescent building block of fluorescent macrocycles [24][25][26][27][28] or cages [29][30][31] in recent years. These cyclic TPE compounds exhibit outstanding performances, which enable them as selectivity sensors, 32 molecular storage materials, 33 and supramolecular catalysts.…”
Section: Introductionmentioning
confidence: 99%